Efektivitas Ekstrak Padina minor dalam Meningkatkan Kadar Klorofil Pada Tanaman Sorgum - Yourga, Anze; Chaniago, Irawati; Kasim, Musliar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Sorghum is a potential alternative food source due to its high carbohydrate, fiber, and protein content, which surpasses that of rice, as well as its greater adaptability to marginal land and dry weather conditions. However, sorghum productivity is often hindered by suboptimal fertilizer use, necessitating additional solutions like biostimulants. Seaweed-based biostimulants, such as Padina minor, hold promise in enhancing plant growth by stimulating nutrient absorption, improving resistance to abiotic stress, and enriching soil quality. This study aimed to evaluate the effectiveness of P. minor extract in increasing chlorophyll levels in sorghum plants. The experiment was conducted using a Completely Randomized Design (CRD) with varying concentrations of P. minor extract (20%, 30%, and 40%) and application frequencies (1, 2, and 3 times). The research results showed that (1) a concentration of 20% with administration of the extract once gave a significant increase in chlorophyll levels compared to other concentrations and frequencies; (2) administration of biostimulants in low concentrations and with fewer administration frequencies has proven to be more effective; (3) higher concentrations and frequencies of biostimulants can cause toxicity to plants; (4) the use of P. minor extract as a biostimulant can be a sustainable alternative in agricultural practices to improve the quality and productivity of sorghum.